O comércio de origem chinesa e o espaço comercial da Varziela (Vila do Conde) - Guimarães, Susana Raquel (2009)
When The People's Republic of China was admitted as a new member of the World Trade Organization, at the end of 2001 and the quota system that regulated his products was abolished, that had significant effects worldwide and also in Portugal, where the increase on imports created an ethnic retail subsystem composed of an increasing number of shops and warehouses specially dedicated to sell products originated in China. In this context, in the North of Portugal, the Industrial Zone of Varziela, in the Municipality of Vila do Conde, 20km distant from Porto and only 16km from the port of Leixões, is restructured and receives an increasing number of warehousing and selling units that nowadays totalize 197. This is at the centre of the present text, where a multiescalar approach is conducted before concentrating the attention on Varziela, trying to contribute to understand the emergence and internal structure of this very special area of the North West of Portugal.